2014
DOI: 10.1183/09031936.00153613
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of exercise pulmonary haemodynamics in pulmonary arterial hypertension

Abstract: The aim of the study was to investigate the prognostic value of right heart catheterisation variables measured during exercise.55 incident patients with idiopathic, familial or anorexigen-associated pulmonary arterial hypertension (PAH) underwent right heart catheterisation at rest and during exercise and 6-min walk testing before PAH treatment initiation. Patients were treated according to recommendations within the next 2 weeks. Right heart catheterisation was repeated 3-5 months into the PAH treatment in 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 30 publications
(39 reference statements)
4
68
1
3
Order By: Relevance
“…The predominant cardiovascular abnormality of PAH on exercise is that of a failure to augment cardiac output on exercise due to increased right ventricular afterload, and this in turn is largely due to a failure to augment cardiac stroke volume [7]. Unlike in healthy subjects, where pulmonary vascular resistance falls on exercise due to pulmonary vascular recruitment and distensibility of the resistive vessels [8], the pulmonary vascular resistance does not fall in PAH to accommodate rises in cardiac output and pulmonary arterial pressure.…”
Section: Cardiovascular Response To Exercise In Pahmentioning
confidence: 99%
See 1 more Smart Citation
“…The predominant cardiovascular abnormality of PAH on exercise is that of a failure to augment cardiac output on exercise due to increased right ventricular afterload, and this in turn is largely due to a failure to augment cardiac stroke volume [7]. Unlike in healthy subjects, where pulmonary vascular resistance falls on exercise due to pulmonary vascular recruitment and distensibility of the resistive vessels [8], the pulmonary vascular resistance does not fall in PAH to accommodate rises in cardiac output and pulmonary arterial pressure.…”
Section: Cardiovascular Response To Exercise In Pahmentioning
confidence: 99%
“…In fact, several studies have been able to demonstrate that this aggregate of pathophysiological abnormalities contains relevant prognostic information. The absence of an adequate right ventricular contractile reserve [9] as well as the failure to increase systemic blood pressure during exercise [10] have been identified as predictors of poor prognosis, whereas greater increases in exercise cardiac output and systolic pulmonary arterial pressure identify better prognosis and response to therapy [7,11].…”
Section: Cardiovascular Response To Exercise In Pahmentioning
confidence: 99%
“…The anterior axillary line served as the zero reference in all supine measurements [28] . During constant workload, 3 min after the start of exercise, the measurements of exercise hemodynamic parameters were performed, with a total duration of approximately 5-7 min [19] . Pulmonary pressures were averaged over several respiratory cycles during the constant workload under exercise [29] .…”
Section: Right Heart Catheterizationmentioning
confidence: 99%
“…Along these lines, the echocardiographic parameter 'notch ratio', which describes the pulmonary arterial blood flow pattern, was shown to predict residual PH 3 months after PEA [17] , whereas resting hemodynamic parameters before PEA did not correlate with hemodynamic parameters after PEA [18] . In idiopathic pulmonary arterial hypertension (PAH), recently published data indicate a superiority of exercise pulmonary measurements as prognostic factors [19] . Moreover, in a small cohort of CTEPH patients with persistent dyspnea after PEA but normal pulmonary hemodynamics at rest, the diminished pulmonary arterial compliance (Cpa) during exercise was a strong predictor of limited functional capacity [20] .…”
mentioning
confidence: 99%
“…In a prospective, 4-year follow-up study that identified PAH in 89 (12%) out of 722 patients with SSc using RHC, elevated mean RAP was reported to be the strongest haemodynamic predictor of mortality among the SSc-PAH group ( p=0.0001) [53]. In addition, preliminary evidence suggests that exercise haemodynamics during RHC, as previously discussed, may be a more accurate predictor of long-term outcome than haemodynamic variables recorded at rest in patients with PAH [6,54].…”
Section: Evolving Utilisation and Application Of Rhc In Clinical Pracmentioning
confidence: 82%